Identifikasi Faktor yang Mempengaruhi Penerapan Safety Surgery Cheklist : Narative Review - Risfi Ariyanti; Novita kurniasari (Malahayati Nursing Journal, 2026)
ABSTRACT The Surgical Safety Checklist (SSC) is globally recognized for its ability to reduce mortality rates and postoperative complications. However, its effectiveness is often hindered by low actual compliance, administrative burdens, and cultural resistance within the operating room. Innovations such as AI based VoiceCheck technology are emerging as solutions to overcome physical and documentation barriers. This study aims to identify the factors influencing compliance variability, evaluate the effectiveness and implementation barriers of the SSC in enhancing patient safety, and analyze the influence of organizational culture, managerial support, and the integration of AI based digital innovations (VoiceCheck) on staff compliance levels in the operating theater. This study employs a narrative review method to synthesize qualitative and quantitative data. The analysis focuses on key themes by reviewing recent studies regarding safety culture, administrative interventions, and technological innovations in perioperative procedures. The analysis reveals that compliance with SSC forms is significantly influenced by senior leadership support and the establishment of a culture characterized by open communication (psychological safety). The study identifies a substantial discrepancy between administrative compliance in medical documentation (89%) and actual verbal implementation in practice (47%), a phenomenon often attributed to increased workload and the necessity of multitasking. The use of AI-enhanced VoiceCheck technology (specifically the Whisper V3 model) demonstrated remarkable precision (94.8%) and maintains sterility through handsfree functionality, although challenges regarding environmental noise persist. Furthermore, proactive patient participation and the customization of checklists for specific specialties have been shown to increase patient ownership and emotional security. The success of the SSC is not merely a matter of paperwork; it is the result of synergy between continuous administrative interventions, the reinforcement of a respect-based work culture, and the utilization of digital assistants. Hospitals must conduct regular audits and team-based training to bridge the gap between formal reporting and actual clinical practice for sustainable patient safety. Keywords: Surgical Safety Checklist, Patient Safety, Staff Compliance, Organizational Culture, VoiceCheck, AI.  ABSTRAK Surgical Safety Checklist (SSC) telah diakui secara global mampu menurunkan angka mortalitas dan komplikasi pascaoperasi. Namun, efektivitasnya sering kali terhambat oleh rendahnya kepatuhan aktual, beban administratif, dan resistensi budaya di ruang operasi. Inovasi seperti teknologi VoiceCheck berbasis AI mulai muncul sebagai solusi untuk mengatasi hambatan fisik dan dokumentasi.. Studi ini bertujuan untuk mengidentifikasi faktor-faktor yang memengaruhi variabilitas kepatuhan, mengevaluasi efektivitas dan hambatan implementasi Surgical Safety Checklist(SSC) dalam meningkatkan keselamatan pasien, serta menganalisis pengaruh budaya organisasi, dukungan manajerial, dan integrasi inovasi teknologi digital berbasis AI (VoiceCheck) terhadap tingkat kepatuhan staf di ruang operasi. Metode: Penelitian ini menggunakan metode tinjauan naratif untuk menyintesis data kualitatif dan kuantitatif. Analisis difokuskan pada tema-tema utama dengan menganalisis berbagai studi terkini mengenai budaya keselamatan, intervensi administratif, dan inovasi teknologi dalam prosedur perioperatif. Analisis mengungkapkan bahwa kepatuhan terhadap Formulir  SSC secara signifikan dipengaruhi oleh dukungan kepemimpinan senior dan pembentukan budaya yang ditandai dengan komunikasi terbuka (aman secara psikologis). Ini mengidentifikasi perbedaan substansial antara tingkat kepatuhan administratif dalam dokumentasi medis (89%) dan implementasi verbal aktual dalam pengaturan praktik (47%), sebuah fenomena yang sering dikaitkan dengan peningkatan beban kerja dan perlunya multitasking. Penggunaan teknologi VoiceCheck yang ditingkatkan AI (model Whisper V3) menunjukkan presisi yang menonjol (94,8%) dan mampu menjaga sterilitas melalui fungsi handsfree, meskipun tantangan yang ditimbulkan oleh kebisingan lingkungan tetap ada. Selain itu, partisipasi proaktif pasien dan penyesuaian daftar periksa untuk spesialisasi tertentu telah ditunjukkan untuk meningkatkan rasa memiliki dan keamanan emosional pasien. Keberhasilan SSC bukan sekadar masalah pengisian dokumen, melainkan hasil sinergi antara intervensi administratif yang berkelanjutan, penguatan budaya kerja berbasis respek, dan pemanfaatan asisten digital. Rumah sakit perlu melakukan audit rutin dan pelatihan berbasis tim untuk menutup celah antara pelaporan formal dan praktik klinis nyata demi keselamatan pasien yang berkelanjutan. Kata Kunci: Surgical Safety Checklist, Keselamatan Pasien, Kepatuhan Staf, Budaya Organisasi, VoiceCheck, AI.